Sosialisasi Strategi Peningkatan Kualitas Pendidikan Melalui Metode Pembelajaran Kreatif dan Inovatif di Desa Rantau Bintang - Muhammad Zulkar Syahfitra; Yuria Nadila; Fatia Sari; Ahmad Zaki; Hayatun Sabariah (peduli riset dan pengabdian masyarakat, 2024)
Education is the most important thing nowadays, with education humans can become quality human beings and be able to live a good life. To make this happen, as a teacher/educator you must strive for student success in learning. Method of implementing KKN service by STAI Jam'iyah Mahmudiyah Tanjung Pura students in Rantau Bintang Village KEC.Bandar Pusaka KAB.Aceh Tamiang regarding